2013
DOI: 10.4254/wjh.v5.i10.577
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis in HBV and HCV patients: Clinical characteristics and outcome

Abstract: AIM:To present the characteristics, management and outcome of patients with hepatitis B virus (HBV) or hepatitis C virus (HCV) infections concurrent with primary biliary cirrhosis (PBC). METHODS:Since January 2001 to September 2009, we retrospectively evaluated the medical records of all HBV (n = 1493) and HCV patients (n = 526) who are followed in our center for the presence of concurrent PBC. Seventeen patients identified with concurrent viral hepatitis and PBC (8 HCV and PBC; follow-up: 61 ± 37 mo and 9 HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Remarkably, the current study demonstrates aggravation of liver disease by intracellular HBsAg accumulation without viral infection in case of simultaneous labefaction. Primary biliary fibrosis and biliary atresia with additional HBV infection has been described in clinical studies [ 24 , 25 ]. In addition, biliary diseases might even be attributed or caused by HBV infection [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the current study demonstrates aggravation of liver disease by intracellular HBsAg accumulation without viral infection in case of simultaneous labefaction. Primary biliary fibrosis and biliary atresia with additional HBV infection has been described in clinical studies [ 24 , 25 ]. In addition, biliary diseases might even be attributed or caused by HBV infection [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in identifying hepatitides C virus (HCV) and/or HBV infections in PBC patients is such that an accurate diagnosis of PBC is usually observably delayed in this particular patient cohort[71]. In PBC patients with accompanying HCV infection, impact therapy might be approved in consideration of the relevant and more serious cirrhosis[72].…”
Section: Fat-soluble Vitamin Deficiencymentioning
confidence: 99%
“…In PBC patients with accompanying HCV infection, impact therapy might be approved in consideration of the relevant and more serious cirrhosis[72]. A retrospective Greek study showed that, among 1493 HBV and 526 HCV patients, 17 were confirmed as having a coexistence of viral hepatitides and PBC (8 cases of HCV and 9 cases of HBV)[71]. It is very difficult to make an exact diagnosis of PBC in HBV or HCV-infected patients, meaning that a precise diagnosis is usually delayed[71].…”
Section: Fat-soluble Vitamin Deficiencymentioning
confidence: 99%
See 2 more Smart Citations